Gender Cognitive and Behavioral Asymmetry in Translating - Zasiekin, Serhii; Zasiekina, Dariia (East European Journal of Psycholinguistics, 2016)
The present paper outlines results of a psycholinguistic study of gender cognitive and behavioral tendencies reflected in a specially compiled bilingual corpus of translated and original texts of fiction. The authors attempt to show how gender can affect translator’s choices in English - Ukrainian literary translation. A special focus is on S-universals (Chesterman, 2011), since their study gives a direct access to translators’ mental operations. Explication, simplification on the lexical and syntactic levels, the use of more frequent lexis in the target texts, lack of repetitions, avoidance of culture-bound terms, standardizing, and convergence belong to a group of the main gender-dependent translation S-universals. Among the most typical findings of the research are women’s better flexibility in the translation viewed as a metacognitive universal of their “global” thinking, i.e. a synthetic cognitive style. Female translators have shown higher indices of target text lexical density, explicitation and nominalization. By contrast, male translators tend to avoid nominalizations, being more accurate when reproducing certain source text units, thereby opting for a semantic method (Newmark, 1988) of translation. This universal strategy manifests their analytical cognitive style. When translating the status-asymmetrical conversations in the source text, where fictional characters perform socially marked or blurred roles, men aim at retaining negative politeness in their target language versions. References Бендас Т. В. Гендерная психология. – СПб.: Питер, 2007. Bendas, T. (2007). Gendernaya Psikhologiya [Gender Psychology]. St. Petersburg: Piter. Карасик В. И. Социальный статус человека в лингвистическом аспекте // “Я”, “Субъект”, “Индивид” в парадигмах современного языкознания. – М. : ИЯ РАН, 1992. – С. 47–74. Karasik, V. I. (1992). Sotsialnyi status cheloveka v lingvisticheskom aspekte [Human social status in linguistic aspect] ‘Ya’, ‘Subjekt’, ‘Individ’ v Paradigmakh Sovremennogo Yazykoznania, 47–74. Кутузов А. Переводы мужские и женские: есть ли разница? (на материале Корпуса несовершенных переводов)/А. Кутузов // Проблемы перевода, лингвистики и литературы. – 2012. – Вып. 15, № 1. – С. 97-104. Kutuzov, A. (2012). Perevody muzhskiye i zhenskiye: yest li raznitsa? [Male and female translations: Any difference?]. Problemy Perevoda, Lingvistiki i Literatury, 15(1), 97-104. Сорокин Ю. А. Переводоведение: статус переводчика и психогерменевтические процедуры. – М. : МТДК «Гнозис», 2003. – 160 с. Sorokin, Yu. A. (2003). Perevodovedeniye: Status Perevodchika i Psikhogermenevticheskiye Procedury [Translation Studies: Translator’s Status and Psychohermeneutic Procedures]. Moscow: Gnozis. 5. Холод А. М. Речевые картины мира мужчин и женщин. – Днепропетровск : Пороги, 1997. – 229 с. Kholod, A. M. (1997). Rechevye kartiny mira muzhchin i zhenshchyn [Speech world view of men and women]. Dnepropetrovsk: Porogi. Холодная М. А. Когнитивные стили: О природе индивидуального ума. – М. : ПЕР СЭ, 2002. – 304 с. Kholodnaya М. А. (2002). Kognitivnye Stili: O Prirode Individualnogo Uma [Cognitive Styles: On the Nature of Individual Mind]. Мoscow: PERSE. Arabski, J. (2013). Psycholinguistic and neurobiological differences between males and females. Proceedings of the 10th International Congress of the ISAPL (423). Baker, M. (1999). The role of corpora in investigating the linguistic behaviour of translators. International Journal of Corpus Linguistics, 4(2), 281–298. Berman, A. (1990). La retraduction comme espace de traduction. Palimpsestes, 4, 1–7. Blum-Kulka, S. (1986). Shifts of cohesion and coherence in translation. In: Interlingual and Intercultural Communication (pp. 17–35). J. House, S. Blum-Kulka, (Eds). Tübingen: Narr. Brown, P., Levinson, S. (1987). Politeness: Some Universals in Language Usage. Cambridge: Cambridge University Press. Chesterman, A. (2000). A causal model for Translation Studies. In: Intercultural Faultlines: Research Models in Translation Studies I: Textual and Cognitive Aspects (pp. 15–27). M. Olohan, (Ed). Manchester: St. Jerome. Denturck, K. (2012). Explicitation vs. implicitation: a bidirectional corpus-based analysis of causal connectives in french and dutch translations. Across Languages and Cultures, 13(2), 211–227. Desmidt, I. (2009). (Re)translation revisited. Meta: Translators’ Journal, 54(4), 669–683. Leonardi, V. (2007). Gender and Ideology in Translation. Do Women and Men Translate Differently? A Contrastive Analysis from Italian into English. Bern: Peter Lang AG. Laviosa, S. (2002). Corpus-based Translation Studies. Theory, Finding, Applications. Amsterdam; Atlanta: Rodopi. Newmark, P. (1988). Approaches to Translation. London: Prentice Hall. Olohan, M. (2002). Leave it out! Using a comparable corpus to investigate aspects of explicitation in translation. Cadernos de Tradução, 9, 153–169. Vinay, J. & Darbelnet, J. (1995). Comparative Stylistics of French and English. Translated by J. C. Sager and M. J. Hamel. Amsterdam: John Benjamins. Zasiekin, S. (2016). Understanding translation universals. Babel: International Journal of Translation, 62(1), 122–134. Sources Bradbury, R. The Smile. Retrieved from: http://raybradbury.ru/library/ story/52/9/1/ Bradbury, R. (1983). Fahrenheit. Short Stories. Moscow: Raduga Publishers, 1983. – 382 p. Бредбері Р. Усмішка / пер. з англ. Л. Коломієць // Всесвітня література в середніх навчальних закладах України. К.: Педагогічна преса, 1999. № 3 (227). С. 11–12. Bradbury, R. (1999). Ousmishka [The Smile] / translated by L. Kolomiyets. Vsesvitnia Literatura v Serednikh Navchalnykh Zakladakh Ukrainy, 3(227), 11–12. Бредбері Р. Усмішка / пер. з англ. А. Веприняка // Зарубіжна література. 6 клас. Посібник-хрестоматія. Тернопіль: Навчальна книга – Богдан, 1999а. С. 296–300. Bradbury, R. (1999). Ousmishka [The Smile] / translated by Yaroslav Vepryniak. Zarubizhna Literatura. 6th Form, 296–300. Бредбері Р. Усмішка / пер. з англ. А. Євси // Світова література. 6 клас. Хрестоматія / Упорядник Гарбуз В. М. ; наук. ред. Таранік-Ткачук К. В. – Харків : ФОП Співак В. Л., 2011. – С. 374–381. Bradbury, R. (2011). Ousmishka [The Smile] / translated by Andrii Ievsa. Svitova Literatura. 6th Form. Textbook, 374–381. Браун Д. Код да Вінчі. – Х.: Клуб сімейного дозвілля, 2006. Brown, D. (2006). Kod da Vinchi [The Da Vinci Code] / translated by A. Kamianets’. Kharkiv: Club Simeinoho Dozvillia. Браун Д. Код да Вінчі. // Всесвіт. – 2006. – № 1–4, 11–12. – К. : Всесвіт. Brown, D. (2006). Kod da Vinchi [The Da Vinci Code] / translated by V. Shovkun. Vsesvit, 1–4, 11–12. КТУМ: Корпус текстів української мови / [Електронний ресурс]. Режим доступу: http://www.mova.info/corpus.aspx?l1=209 Korpus Tekstiv Ukrains’koyi Movy [The Corpus of the Ukrainian Language] / [Electronic Resource]. Retrieved from: http://www.mova.info/corpus.aspx?l1=209 Slovnyk Ukrainskoyi Movy [Dictionary of the Ukrainian Language] / I. K. Bilodid, ed. – Vol. 5. Kyiv: Naukova Dumka. – P. 36, 100. Tolkien J. R. R. (1954). The Fellowship of the Ring. L.: George Allen & Unwin. Толкін Дж. Р. Р. Володар Перснів: Хранителі Персня / пер. з англ. А. Немірової. Харків: Фоліо, 2003. Толкін Дж. Р. Р. Старий ліс: Уривок з епопеї «Володар Перснів» / пер. з англ. А. Веселовського // Всесвіт. 2006. №№ 11–12, 124–135. Tolkien, J. R. R. (1981). The Hobbit, or, There and Back Again. L. : Unwin. Толкін Дж. Р. Р. Гобіт, або Туди і Звідти / пер. з англ. О. О’Лір. – Львів: Астролябія, 2012. Tolkien, J. R. R. (2012). Hobit abo Tudy i Zvidty [The Hobbit, or There and Back] / translated by Оlena О’Lear. Lviv: Astroliabia. Толкін Дж. Р. Р. Гобіт, або Мандрівка за Імлисті гори / пер. з англ. О. Мокровольського. – К. : Веселка, 1985. Tolkien, J. R. R. (1985). Hobit abo Mandrivka za Imlysti Hory [The Hobbit, or a Trip Beyond the Misty Mountains] / translated by Оlexandr Mokrovols’kyi. Кyiv: Veselka. 6. Brown, D. (2003). The Da Vinci Code. L. : Corgi Books.